Issues in the Justiciability of the Right to Health (2019)
The judicialization of health care is increasing dramatically in the last decade worldwide. Although this judicial activism has undoubtedly contributed to guaranteeing the protection of this right, many challenges remain despite this progress. The objective of this book is to evaluate the different challenges and opportunities that States have in the protection of the Right to Health while maintaining a balanced level of judicial activism. More specifically, it looks to identify in what contexts judicial activism is justified in order to protect the right to health by analysing the dynamics of litigation as well as its consequences. The book starts by presenting a case in Spain. Juan Antonio Maldonado shows how conflicts between different institutions might arise as a result of disagreements about the protection of the right to health in contexts of economic crisis. As a result of that, the Court had to make difficult decisions about how to solve such conflicts. It then presents an experience in Slovakia, Central Europe. Barbara Pavlíkova examines the Health system in Slovakia describing how the health system has evolved in this country after the fall of communism and how the health system is currently being affected by many factors. In a similar vein, Cippitani and Colcelli focus on the topic of Social Rights and how they are recognized in the Italian context, and finally, Rodolfo Gutiérrez examines the case of Colombia, scrutinizing how the system, despite expanding its level of coverage, is currently generating a high level of judicialization of health. The concluding chapter carries out a comparative analysis of the cases studied in order to generate some recommendations.